Behaviour Modification: An Efficacious Tool of Shaping Individual Behaviour Productive and Supportive to Organizational Goal Attainment - Bharijoo, Surendra Bahadur (Journal of Nepalese Business Studies, 2009)
This article intends to shed light on the basic concept of Behaviour Modification which is drawing attention increasingly of managers and practioners in shaping behavior of people with whom they are dealing constantly in the organization. Researches and studies revealed that Behaviour Modification can be an efficacious tool in modeling individual behaviours if it is appropriately used with caution. As such, it is also attempted to present here the basic steps and guidelines for its application. In addition to these, the article attempts to point out experiences and limitations of application of Behavioural Modification as explained by its researchers. Key words: Behaviour, modification, individual, organization, goal attainment. The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 50-61